An Overview of Post-Fertilization Parental Care in Gobiidae - Miguel Trujillo-García; Bertha Patricia Ceballos-Vázquez; Palestina Guevara-Fiore; Hope Klug (Diversity)
Parental care increases offspring survival but is typically costly to the parent providing it. Understanding diversity in parental care across animals is a timely topic in evolutionary ecology. Fishes are particularly well suited for studies aimed at understanding the diversity of parental care because parental care in fishes is highly variable across species. In most fish species, no care is provided. When parental care is provided, it is often paternal, although biparental and maternal care occur in some fish species as well. Parental care in fishes ranges from simple guarding of eggs in a territory to prolonged care of young after hatching. Within fishes, gobies are thought to exhibit diverse parental care. In the current manuscript, we begin to synthesize our knowledge of patterns of parental care in gobies by providing a review of the parental care strategies that are exhibited by gobiid species. Our review reveals that parental care in gobies most often includes guarding, fanning, and cleaning, although some species engage in other types of care such as larval release, the production of antimicrobial substances, and the construction of post-mating mounds. Care in gobies is most often paternal, but maternal and biparental care have been documented in some species.